2016
DOI: 10.1007/s00210-016-1330-7
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide attenuates partial warm ischemia-reperfusion injury in rat livers

Abstract: Ischemia-reperfusion (IR) injury constitutes the most important cause of primary dysfunction of liver grafts. In this study, we have addressed the possible hepatoprotective action of liraglutide against partial warm hepatic IR injury in male rats. Rats were randomly assigned into: sham, IR, and liraglutide-pretreated IR groups. Liraglutide was administered 50 μg/kg s.c. twice daily for 14 days, and then, hepatic IR was induced by clamping portal vein and hepatic artery to left and median lobes for 30 min follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…In the present research, the administration of recombinant GLP1 in non-steatotic DCDs was associated with exacerbated damage, inflammation, and cell proliferation failure. Our results disagree with current research results that are mainly focused on administration of GLP1 analogs and which have demonstrated beneficial effects on non-steatotic livers suffering pathologies such as hepatic warm ischemia, thus suggesting a clinical importance for GLP1 as a therapeutic strategy [4]. The reason for the disparity in these results might be related to the type of ischemia involved, since it is well known that the molecular mechanisms implicated in warm hepatic I/R injury trigger different pathways than in cold I/R injury [29].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present research, the administration of recombinant GLP1 in non-steatotic DCDs was associated with exacerbated damage, inflammation, and cell proliferation failure. Our results disagree with current research results that are mainly focused on administration of GLP1 analogs and which have demonstrated beneficial effects on non-steatotic livers suffering pathologies such as hepatic warm ischemia, thus suggesting a clinical importance for GLP1 as a therapeutic strategy [4]. The reason for the disparity in these results might be related to the type of ischemia involved, since it is well known that the molecular mechanisms implicated in warm hepatic I/R injury trigger different pathways than in cold I/R injury [29].…”
Section: Discussioncontrasting
confidence: 99%
“…GLP1 is then secreted and released into the circulation via portal vein, thus reaching the liver [3]. It has been reported that GLP1 exhibited protective effects against ischemia-reperfusion (I/R) damage, since treatment with a GLP1 analog resulted in anti-inflammatory actions and inhibition of cell death in non-steatotic rats undergoing hepatic partial warm ischemia [4]. To the best of our knowledge, there are no studies of GLP1 effects in experimental models of LT using DCD organs, either non-steatotic or steatotic.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1), a well-known molecule released from gut enteroendocrine cells, can regulate meal-related glycemic excursions by augmenting insulin production and inhibiting glucagon secretion [6]. Additionally, mounting evidence has shown that GLP-1 analogs/ GLP-1 receptor (GLP-1R) agonists reduce obesity-induced chronic kidney injury via restoration of renal metabolism homeostasis [7], ameliorate renal injury resulting from diabetic kidney disease [8], attenuate neuronal death in early brain injury after subarachnoid hemorrhage [9], relieve myocardial damage by promoting autophagy [10], alleviate reperfusion injury-induced acute myocardial infarction [11,12], and protect liver from ischemiareperfusion injury [13]. Furthermore, GLP-1 analogs/ GLP-1R agonists modulate tumor necrosis factor-α (TNFα)-mediated endothelial activation [14], inhibit highglucose-induced oxidative injury of vascular ECs [15], protect cardiac microvascular ECs against hypoxia/reoxygenation injury [16], and strengthen the barrier integrity in ECs [17].…”
Section: Introductionmentioning
confidence: 99%
“…tGSH and MDA levels in the benidipine group were very close to those of the sham surgery group, suggesting that benidipine maintained the oxidant/antioxidant balance in liver tissue at physiological levels. In the literature, it has been reported that tGSH decreases significantly in IR treated liver tissue with high MDA levels [11,25]. In addition, some authors have argued that benidipine protects ovarian tissue from IR oxidative damage by preventing MDA increase and tGSH decrease [9,24].…”
Section: Mda and Tgsh Levelsmentioning
confidence: 99%